No Tillage With Plastic Re-mulching Maintains High Maize Productivity via Regulating Hydrothermal Effects in an Arid Region - Yin, Wen; Chai, Qiang; Guo, Yao; Fan, Hong; Fan, Zhilong; Hu, Falong; Zhao, Cai; Yu, Aizhong; Coulter, Jeffrey A. (Frontiers in Plant Science, 2021)
Plastic is a valuable mulching measure for increasing crop productivity in arid environments, however, little is known about the main mechanism by which this valuable technology actuates spatial-temporal changes in soil hydro-thermal effect. So, a three-year field experiment was conducted to optimize soil hydro-thermal effect of maize field with three plastic mulched management treatments: 1) no tillage with plastic re-mulching (NM), 2) reduced tillage with plastic mulching (RM), 3) conventional tillage with annual new plastic mulching (CM). The results showed that NM treatment increased soil water content by 6.6-8.4% from maize sowing to seedling stage, compared to CM, it created a good soil moisture environment for sowing of maize. Also, NM had greater soil water content by 4.8-5.6% from maize silking to early-filling stage than that of CM, it made up for the abundant demand of soil moisture for the vigorous growth of maize filling stage. The NM treatment increased water consumption (WC) before maize big-flare stage, decreased WC from big-flare to early-filling stage, and increased WC after early-filling stage. So, NM treatment effectively coordinated water demand contradiction of maize at entire growing season. NM decreased soil accumulated temperature (SAT) by 7.0-13.0% at maize sowing to early-filling stage compared to CM, but NM had little influence on the SAT during filling stage. In particular, the treatment on NM had smaller absolute values of air-soil temperature differences than RM and CM treatments during maize filling stage, it indicating that NM treatment maintains the relative stability of soil temperature for ensuring grain filling of maize. The NM treatment allowed the maize to grow in a suitable hydro-thermal status, and still maintained high-yield. In addition, NM treatment obtained higher net income and rate of return by 6.4-11.0% and 44.1-54.5% than that of CM, because NM treatment mainly decreased the input costs for plastic and machine operations. Therefore, the NM treatment can be recommended as a promising technique to overcome simultaneous heat stress and water shortage in arid environments.